Genome‐wide DNA methylation analysis of colorectal adenomas with and without recurrence reveals an association between cytosine‐phosphate‐guanine methylation and histological subtypes - Fiedler, David; Hirsch, Daniela; Hajj, Nady El; Yang, Howard H.; Hu, Yue; Sticht, Carsten; Nanda, Indrajit; Belle, Sebastian; Rueschoff, Josef; Lee, Maxwell P.; Ried, Thomas; Haaf, Thomas; et al. (Genes, chromosomes & cancer, 2019)
Aberrant methylation of DNA is supposed to be a major and early driver of colonic adenoma development, which may result in colorectal cancer (CRC). Although gene methylation assays are used already for CRC screening, differential epigenetic alterations of recurring and nonrecurring colorectal adenomas have yet not been systematically investigated.
Gesehen am 19.01.2021